Penerapan Konseling Adlerian Dalam Mengatasi Perilaku Membolos Pada Siswa Man 3 Medan - Risydah Fadilah; Dhea Aulia Putri; Dwi Amalia Susilo; Fara Naia Salsabila (Lembaga Pengembangan Kinerja Dosen, 2023)
According to Adler, living things are an inseparable social unit. They relate to the social cooperation around them, placing the general welfare ahead of their own desires, and achieving a stronger way of life within social organization. Adler made a major contribution to thinking, namely, firstly, he emphasized the social factor of behavior, secondly, the concept of self-creation, and thirdly, the characteristics of each personality. Adler further developed these main points so that they became the characteristics of Adlerian thought, namely: a) the purpose of life, b) the ego drive, c) feelings of inferiority, d) the societal impulse, e) lifestyle, and f) creative power. The basics of Alfred Adler's personality theory assume that individuals and their life problems are always social, such as belonging to other people and paying attention to the welfare of that person.